Flavonic dark matter - Abbas G.; Adhikari R.; Chun E.J. (My University, 2025)
We show for the first time that a common solution to dark matter and the flavor problem of the standard model can be obtained in the framework of the ZN×ZM flavor symmetry where the flavonic Goldstone boson of this flavor symmetry acts as a good dark matter candidate through the misalignment mechanism. A hierarchical mass pattern of quarks and charged leptons naturally follows from the discrete symmetry. For light active neutrinos, we construct the Dirac-type mass matrix which is preferred to fit the observed neutrino oscillation data with normal hierarchy. Our model predicts the axionlike photon coupling characteristically different from the standard QCD axion, which could be probed by the future x-ray or radio observations. © 2023 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the "https://creativecommons.org/licenses/by/4.0/"Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Funded by SCOAP3.